Efficient sorbents based on magnetite coated with siliceous hybrid shells for removal of mercury ions - Tavares, Daniela S.
New sorbents based on magnetite particles coated with siliceous shells were synthesized and tested in the removal of mercury ions from aqueous solutions by magnetic separation. Atomic fluorescence spectroscopy studies performed on water samples treated with these sorbents have shown that the metal ion concentration decreased to values lower than the guideline values for drinking water. The high adsorption affinity for mercury ions in these materials was attributed to dithiocarbamate groups grafted over the siliceous domains using a new surface modification method. Hence, the magnetic particles have been coated with amorphous silica shells that include thiolate moieties via a hydrolytic co-condensation process using tetraethoxysilane (TEOS) and siloxydithiocarbamate (SiDTC) as the sol-gel precursors. This one-step method for the surface modification of magnetite particles led to sorbents with extensive thiolate moieties that can be then collected by applying an external magnetic field.